Strategies for Streamlined Urban Development: A Case Study of Land Use Succession in Upper Hill, Nairobi - Elizabeth Nguah; Owiti K’Akumu (Alanya Üniversitesi, 2024)
This study examines the dynamics of Urban Land Use Succession (ULUS) in Upper Hill, Nairobi, highlighting the impact of neoliberal policies and private sector-led urban redevelopment. It investigates how land tenure, public infrastructure, and planning controls shape urban landscapes, leading to patchwork land use patterns and environmental misalignments. The case of Upper Hill, transitioning from a serene residential area to a bustling commercial hub, is explored to understand the determinants of ULUS and propose strategies for streamlined urban development. Employing Neoliberal Theory and hypothesis testing, the research identifies spatial policy as the primary driver of ULUS. The study suggests innovative approaches, including land assembly and the establishment of an Urban Redevelopment Authority, to harmonize urban development. These strategies aim to bridge the gap between private and public land development, ensuring coherent urban growth. The research contributes to the understanding of urban redevelopment, particularly in Kenyan contexts, by offering a model that integrates public and private interests. This model serves as a blueprint for managing urban transformation in Nairobi and other similar urban settings, promoting sustainable and equitable urban development.